The Role of the Impostor Phenomenon on Anxiety With Youth Religiosity as a Moderator for Adolescents During the COVID-19 Pandemic - Sihombing, Elisabet Fransiska Dina; Rajagukguk, Robert Oloan; Tj, Jacqueline Marie (Universitas Negeri Malang, 2023)
This research aims to see the influence of the impostor phenomenon on anxiety and youth religiosity in adolescents during the pandemic. The research method uses a quantitative approach with regression techniques. A total of 63 participants selected using the accidental sampling method with an age range of 18–21 years who entered college in 2020 filled out the Clance Impostor Phenomenon Scale (CIPS), State-Trait Anxiety Inventory (STAI), and Central Religiosity Scale (CRS) questionnaires. The research results show that the simultaneous interaction of independent variables on state anxiety is 43.3%, while on trait anxiety, it is 58.9%.